Development of Ammonia Gas Leak Detection and Location Method - Ding Xibo; Wang Ru-yue (Universitas Ahmad Dahlan, 2017)
This paper proposed the gas for industrial ammonia leak diffusion model and the Gauss method of leakage localization. A set of wireless ammonia leak alarm system is composed of sensor node, network coordinator and host used in the industrial field was developed, the purpose is to reduce the loss of property caused by the leakage of ammonia industry. Using the monitoring system to carry out the ammonia leak location simulation measurement experiment, the result shows that the relative positioning error of the monitoring system is about 12%, which meets the needs of industrial production safety monitoring. Using the wireless sensor network to monitor the concentration of ammonia gas and locate the leakage source, it solves the problems of traditional wired alarm system, such as difficult wiring and weak expansibility, which helps to find the leak timely and provides a reference for the emergency rescue work.